0009 Interindividual variation and extended wakefulness in sleepiness after acute and chronic sleep deprivation. (25th May 2022) - Fernandes, Guilherme; Araujo, Paula; Tufik, Sergio; Andersen, Monica
Abstract: Introduction: Sleepiness is a behavioural consequence of sleep pressure and is associated with negative outcomes with interindividual variation, possibly related to central sleep mechanisms. However, there is a lack of evidence linking progressive sleep need and sleepiness with factors of individual variability, which could be tested by total acute and chronic sleep deprivation. Thus, the objective of the study was to investigate the development of sleepiness in sleep deprived mice. Methods: Male C57BL/6J mice were distributed in sleep deprivation, sleep rebound and control groups. Animals underwent acute sleep deprivation for 3, 6, 9 or 12 hours or chronic sleep deprivation for 6 hours for 5 consecutive days. Sleep rebound groups had a sleep opportunity for 1, 2, 3, or 4 hours after acute sleep deprivation or 24 hours after chronic sleep deprivation. During the protocols, sleep attempts were counted to calculate a sleepiness index. After euthanasia, blood was collected for corticosterone assessment. Results: Using the average of group sleep attempts, it was possible to differentiate between sleepy (mean>group average) and resistant animals (mean<group average). Resistant mice were more frequent in all settings. Individual variation accounted for 52% of sleepiness variance during chronic sleep deprivation and extended wakefulness explained 68% of sleepiness variance during acute sleep deprivation. A normal corticosterone peak was observed at the start of the dark phase, independent of sleep deprivation. Conclusion: Different profiles of sleepiness emerged in sleep deprived mice. Sleep deprivation was the main factor for sleepiness during acute sleep deprivation whereas in chronic deprivation individual variation was more relevant. Support (If Any): Our studies are supported by the following funding agencies: AFIP (Associação Fundo de Incentivo à Pesquisa), São Paulo Research Foundation (FAPESP #2017/18455-5 to GLF), Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES - Finance Code 001 to GLF), and CNPq (fellowships to MLA and ST; #169040/2017-8, and #141445/2021-1 to GLF). This study received indirect funding from AFIP and CNPq, which support the department in which the project was conducted.